Climate Change and the World Bank Group : Phase II - The Challenge of Low-Carbon Development - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The first volume of Independent Evaluation Group (IEG) series (IEG 2009) examined World Bank experience with the promotion of the most important win-win (no regrets) energy policies, policies that combine domestic gains with global greenhouse gas (GHG) reductions. These included energy pricing reform and policies to promote energy efficiency. This second phase covers the entire World Bank Group (WBG), including the International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA). It assesses of interventions, from technical assistance to financing to regulatory reform. This project-eye view of activities pertains to all the action areas of the Strategic Framework on Development and Climate Change (SFDCC). The third phase will look at the challenge of adaptation to climate change. The WBG's resources, human and financial, are small compared to the task at hand. The International Energy Agency estimates that developing and transition countries need $16 trillion of energy sector investments over 2008-30 under 'business as usual' operations, plus an additional $5 trillion to shift to an ambitiously low-carbon path. Much more is needed for sustainable land and forest management and for urban transport. So a prime focus of this evaluation is how the WBG can get the most leverage, the widest positive impact on both development and climate change mitigation, from its limited resources.